Development Communication and Extension: The Case of a Premier State University in CALABARZON, Philippines - Medina, Benedict (Future Science / FSH-PH Publications, 2022)
Development communication is realized in extension, and extension activities are also DevCom in nature. This study aimed to describe and narrate that development communication is practiced and realized through extension in Batangas State University – The Philippines’ National Engineering University, CALABARZON, Philippines. This study utilized the descriptive-narrative research design in a qualitative approach. Various literature of the Extension Service Office and DevCom of BatStateU were collected to answer the research objectives. Interview-conversations were also conducted among university extension officials and development communication faculty. It was found out that BatStateU has a rich historical development up to what it is now as The National Engineering University. It offers 12 extension agenda plus 1 - to be approved by the University Board of Regents. And lastly, values and concepts that comprised development communication based from Quebral’s definition in 2012 were embodied in the practice of extension in BatStateU.